Performing arts in prisons : creative perspectives - Balfour, Michael, 1966-; Bartleet, Brydie-Leigh; Davey, Linda; Rynne, John; Schippers, Huib, 1959- (Intellect, 2019)
Performing Arts in Prisons explores prison arts in Australia, the United States, the United Kingdom and Chile, and creates a new framework for understanding its practices. There is a growing body of evidence that suggests music, theatre, poetry and dance can contribute to prisoner wellbeing, management, rehabilitation and reintegration. Performing Arts in Prisons represents a range of distinct perspectives on thesubject, from an inspector of prisons to the voice of the prisoner. The book includes a spectrum of arts approaches and models of practice alongside theory, critical commentary and accounts of personal experience to present a full analysis of the value and effects of creative arts in prison.